Prevalence, characterization and antibiotic resistance of Pasteurella multocida isolated from bovine respiratory infection - Jamali, H.; Rezagholipour, M.; Fallah, S.; Dadrasnia, A.; Chelliah, S.; Velappan, R.D.; Wei, K.S.C.; Ismail, Salmah (Elsevier, 2014)
The objectives of this study were to determine the prevalence, characterization and antibiotic resistance of Pasteurella multocida isolated from calves with respiratory infection in Iran. P. multocida was detected in 141/169 bovine respiratory infection cases on Iranian dairy and beef farms. P. multocida were grouped into serogroups A (126/141), D (12/141), and B (3/141). Of the P.  multocida isolates, all harboured the psl, ompH, oma87, fimA, ptfA, nanB, and nanH genes, 139/141 had hsf-2, and 115/141 pfhA, and tadD. The isolates were most frequently resistant to penicillin G (43/141 resistant isolates; 30.5%) and streptomycin (31/141; 22%).